2014
DOI: 10.1155/2014/809383
|View full text |Cite
|
Sign up to set email alerts
|

An Independence Test Based on Symbolic Time Series

Abstract: An independence test based on symbolic time series analysis (STSA) is developed. Considering an independent symbolic time series there is a statistic asymptotically distributed as a CHI-2 with − 1 degrees of freedom. Size and power experiments for small samples were conducted applying Monte Carlo simulations and comparing the results with BDS and runs test. The introduced test shows a good performance detecting independence in nonlinear and chaotic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In [57], the well-known BDS test is introduced, considered as a powerful test to detect nonlinearity. In [58], a simple and powerful test based on STSA is proposed and the results are compared with the BDS and runs test. On one hand, it is found that BDS is not able to detect processes such as the chaotic Anosov and the stochastic processes nonlinear sign model (NLSIGN), nonlinear autoregressive model (NLAR), and nonlinear moving average model (NLMA).…”
Section: Symbolic Independence Testmentioning
confidence: 99%
See 4 more Smart Citations
“…In [57], the well-known BDS test is introduced, considered as a powerful test to detect nonlinearity. In [58], a simple and powerful test based on STSA is proposed and the results are compared with the BDS and runs test. On one hand, it is found that BDS is not able to detect processes such as the chaotic Anosov and the stochastic processes nonlinear sign model (NLSIGN), nonlinear autoregressive model (NLAR), and nonlinear moving average model (NLMA).…”
Section: Symbolic Independence Testmentioning
confidence: 99%
“…In [58] is applied the distribution of quadratic forms in normal variables presented in [59]. X=(ε 1 /σ,ε 2 /σ,…,ε n /σ) is distributed multivariate normal N(ø,Σ).…”
Section: Symbolic Independence Testmentioning
confidence: 99%
See 3 more Smart Citations